Sepsis – it is all about the platelets - Cox, Dermot (Frontiers in Immunology, 2023)
Sepsis is accompanied by thrombocytopenia and the severity of the thrombocytopenia is associated with mortality. This thrombocytopenia is characteristic of disseminated intravascular coagulation (DIC), the sepsis-associated coagulopathy. Many of the pathogens, both bacterial and viral, that cause sepsis also directly activate platelets, which suggests that pathogen-induced platelet activation leads to systemic thrombosis and drives the multi-organ failure of DIC. In this paper we review the mechanisms of platelet activation by pathogens and the evidence for a role for anti-platelet agents in the management of sepsis.